Evaluation of Direct Cash Assistance (BLT) Policy in Kota Baru Urban Village, Abepura District, Jayapura City - Ohoiwutun, Yosephina; Ilham, Ilham; Kaunang, Reywulan Roosmawattie (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to evaluate the implementation of the Direct Cash Assistance program in Kota Batu Urban Village. The type of research used is qualitative. Data collection was conducted through interviews, observation, and documentation. The data analysis process was carried out through three stages, namely data reduction, data presentation, and conclusion drawing. The results of this study indicate that the implementation of the direct cash assistance program policy in Kota Baru Urban Village, seen from the indicators of effectiveness, adequacy, implementation, responsiveness and accuracy, can overall be said to have run quite well. However, there are obstacles obtained, such as; lack of clarity regarding the Direct Cash Assistance program, and lack of communication between related parties. As a recommendation, evaluations must continue to be carried out on officers appointed in the field so that they work more effectively, the distribution of assistance is expected to be more evenly distributed to all communities, and build good communication between related parties so that the program can run according to procedures in order to get a good response from the community.